2020
DOI: 10.3390/ijerph17207456
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Credibility of Nutrition and Health Claims: Policy Implications from a Case Study of Mongolian Food Labels

Abstract: Nutrition and health claims should be truthful and not misleading. We aimed to determine the use of nutrition and health claims in packaged foods sold in Mongolia and examine their credibility. A cross-sectional study examined the label information of 1723 products sold in marketplaces in Ulaanbaatar, Mongolia. The claim data were analysed descriptively. In the absence of national regulations, the credibility of the nutrition claims was examined by using the Codex Alimentarius guidelines, while the credibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For example, SSB manufacturers in the Philippines responded to an SSB tax by introducing smaller serve sizes to lower the unit price and maintain consumption 83 . In Mongolia, food companies had not complied with new food standards restricting health claims because the standards did not provide enough specification on nutrition claims that were not permitted (e.g., nutrient criteria) 104 . Other ways food companies were undermining food environment policies included by intensifying marketing of unhealthy alternatives around schools (where sales and marketing of unhealthy foods were restricted within) 105 and by offering branded samples and marketing resources to medical 78 and educational professionals 106 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, SSB manufacturers in the Philippines responded to an SSB tax by introducing smaller serve sizes to lower the unit price and maintain consumption 83 . In Mongolia, food companies had not complied with new food standards restricting health claims because the standards did not provide enough specification on nutrition claims that were not permitted (e.g., nutrient criteria) 104 . Other ways food companies were undermining food environment policies included by intensifying marketing of unhealthy alternatives around schools (where sales and marketing of unhealthy foods were restricted within) 105 and by offering branded samples and marketing resources to medical 78 and educational professionals 106 .…”
Section: Resultsmentioning
confidence: 99%
“…83 In Mongolia, food companies had not complied with new food standards restricting health claims because the standards did not provide enough specification on nutrition claims that were not permitted (e.g., nutrient criteria). 104 Other ways food companies were undermining food environment policies included by intensifying marketing of unhealthy alternatives around schools (where sales and marketing of unhealthy foods were restricted within) 105 and by offering branded samples and marketing resources to medical 78 and educational professionals. 106 They were also reported to engage in philanthropy, for instance by providing critical school infrastructure 106 and "helping" communities.…”
Section: Corporate Pressures On Food Policy Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Canada the percentage has been calculated at 46% (Franco-Arellano et al, 2018), with the increase of front-of-pack (fop) nutrition claims on baby products of 31.4% to 86.6% between 2009 and 2017 (Elliott, 2019). In turn, in Lithuania only 15.7% of products contain NCs (Murniece and Straumite, 2014), whereas in Mongolia this is true for only 10% of products (Chimedtseren et al, 2020). As far as bakery products are concerned, claims are present on 56.3% of 1565 of these in New Zealand (Al-Ani et al, 2016), and 59.6% of bread in Lebanon, with 32.5% representing NCs and 15.3% HCs (Bou-Mitri et al, 2020).…”
Section: Use Of Nutrition and Health Claims Over The Yearsmentioning
confidence: 99%
“…The more consumers value a healthy lifestyle and a healthy diet, the greater their intentions to purchase claim-bearing products (Bower et al, 2003), and, accordingly, the greater their confidence in NHCs themselves (Russo France and Fitzgerald Bone, 2005). However, the credibility of claims may be very low (Chimedtseren et al, 2020). For instance, Klopcic et al (2020) have shown that only 30% of respondents trust claims.…”
Section: Trusting Claimsmentioning
confidence: 99%